Study of the forbidden energy region in solids with diamond structure: Application to Silicon Si - Cabrera, César (2018)
Forbidden power of silicon with crystal structure of diamond is determined indirectly from the electronic structure: energy bands and the density of States both in the ground state T = 0°K. Using the method of the orbital linear Muffin-Tin (LMTO) together with an effective potential of the solid Schrödinger equation was solved and obtained energy bands and the density of States. The minimum total energy -16.85 Ry per unit cell, occurs for maximum transfer of load to empty sphere on the diagonal of the Crystal network. Associated forbidden energy gap is 0.099 Ry which is equivalent to 1.35 eV, a value close to the experimental gap of 1.17 eV that already exists in the literature.